Challenges and Innovations in the Islamic Education System - Antoni, Jono; Hidayah, Jumatul; Yanto, Murni; Istan, Muhammad; Azwar, Beni (Yayasan Corolla Education Centre, 2025)
Examining the issues, developments, and adjustments that the Islamic educational system has made in response to shifting times, global dynamics, and technological breakthroughs is the aim of this research. Data was gathered using a qualitative approach using the library research method, including literature, policy papers, and prior study findings. The results of the theme analysis demonstrate that the Islamic education system faces a variety of issues, both global and national. These problems include the industrial revolution, government regulations, disjointed learning methodologies, and the expectations of 21st-century competence performance. At the national level, the low accreditation and recognition of religious educational institutions is also major obstacle. As a result, several innovations have been developed, including interactive teaching techniques, the adaptable curriculum that combines contemporary science with Islamic ideals, and the use of digital technology in the classroom. In addition, the Islamic education system also shows efforts to adapt to the times through the transformation of educational orientation, the adoption of 21st-century methods, and the integration of intra-, co-, and extra-curricular learning. These findings show that despite facing complex challenges, the Islamic education system in Indonesia has great potential to develop adaptively, innovatively, and relevantly in responding to current and future educational needs.